Towards global consensus on core outcomes for hidradenitis suppurativa research: an update from the HISTORIC consensus meetings I and II. (1st March 2018) - Thorlacius, L.; Garg, A.; Ingram, J.R.; Villumsen, B.; Theut Rii, P.; Gottlieb, A.B.; Merola, J.F.; Dellavalle, R.; Ardon, C.; Baba, R.; Bechara, F.G.; Cohen, A.D.; et al.
Summary: Hidradenitis suppurativa (HS) is an uncommon skin condition that causes painful swollen red bumps in the folds of the body (underarms, under breasts, groin, and buttocks). It can be mistaken for bacterial abscess or boils, but HS is not caused by bacteria. HS occurs in about 0.1–1% people in the US and Europe. The authors include people with HS, dermatologists, surgeons, members of the pharmaceutical industry and medical regulators from 13 countries and four continents. This study aimed to find out what clinical trials for HS should measure, such as symptoms (e.g. pain, itch), physical changes (e.g. skin redness or swelling), or impact on people's lives (e.g. quality of life). To do this, the study included two groups: people with HS and healthcare providers (physicians, pharmaceutical industry representatives, and regulatory representatives) and conducted in‐person meetings with presentations and discussions as well as surveys to gather opinions on which measures to include. The result of the meetings, discussions, and surveys showed that at least 70% of the people with HS and healthcare providers recommended that clinical trials include measures of: (1) physical changes due to HS (e.g. redness); (2) changes in the course of HS (e.g. flare‐ups); (3) quality of life changes due to HS specifically; (4) satisfaction (e.g. satisfaction with treatment) ; (5) pain; (6) other symptoms (e.g. itching); and a global rating (i.e. overall rating, considering everything, of the severity of the condition). This work is important because it included many different types of people who contribute to HS treatment, including the people who have HS, develop or regulate treatments, and treat people with HS. More work is coming, and it will focus on final suggestions on what to measure and how to measure it in trials treating HS.